Amorphous vanadium-doped iron borate/tetraboride hybrid as an efficient electrocatalyst for the oxygen evolution reaction - Ahmed, Tanbir; Pal, Santanu; Sinha, Nibedita; Das, Chandni; Roy, Poulomi (Dalton Transactions, 2026)
The design of an effective electrocatalyst as a replacement for a conventional expensive electrocatalyst for facilitating the sluggish oxygen evolution reaction (OER) at the anode has been identified as an effective way to make hydrogen production economical. Herein, we have developed a unique combination of iron borate and iron tetraboride (Fe-BO/FeB) by a facile chemical reduction process. The optimum vanadium doping further led to the transformation of Fe-BO/FeB into an amorphous form, which is believed to be very beneficial for the OER mechanism. The developed electrocatalyst needs overpotentials of 215 mV and 256 mV in alkaline 1 M KOH electrolyte to achieve current densities of 10 and 100 mA cm-2, respectively, and it also shows stability over 48 h, maintaining a high current density of 200 mA cm-2. Enhanced performances were also confirmed by smaller activation energies for the optimized sample compared with a pristine electrocatalyst.